The Art of Understanding and Implementing Strategic Project Management & Servant Leadership Impacted by ISO 9001:2015 in Indian Manufacturing Public Sectors - Peyyala, Sri Lakshmi (Digital Repository of Theses - SSBM Geneva, 2025)
Purpose: The purpose of this research study is to explores the understanding of the concepts and aims to experiment with the unique combination of Strategic Project Management and Servant Leadership to improve and implement the quality of strategic project management practices and a new skill set on servant leadership impacted by ISO 9001:2015 connected with ISO 21502:2020 for successful project execution in Indian manufacturing public sectors. These emerge by focusing on the necessary areas to improve planning and the existing master documents, such as principles, procedures, guidelines, checklists, work instructions, registers, and formats for organizational management, aiming to develop strategic project management internally and under continuous improvement. Design/methodology/approach: The research goal is to collect data from different resources like International Standard ISO documents, literature reviews, feedback, discussions, interviews with senior experts, ISO 9001:2015 records and policies connected with ISO 21502:2020 analyze the data samples, and practice the positive influences on more structured entities in the project environment. This study uses a qualitative method to analyze the data regarding the unique combination of Strategic Project Management and Servant Leadership impacted by ISO 20502:2020 connected with ISO 9001:2015. The author proposed implementing ISO 21502: 2020 in Indian Public Sector Units (PSUs) for manufacturing. This study involved collecting data from 381 project managers across various PSUs in India. The researcher used statistical techniques such as descriptive statistics to analyze the data. Finding: The exploratory investigation comprised an empirical phase and a theoretical phase. The results show that the implementation of Strategic Project Management and Servant Leadership, by adopting ISO 21502:2020, influences personnel and business growth in Indian Manufacturing Public Sector Units. Finally, the researcher found that 201 (48.6%) out of 412 participants positively supported the conceptual theory of Servant leadership of Project managers and recommended the implementation of ISO 21502:2020 as a part of continual improvement connected with ISO 9001:20215 in the project-oriented organization for benefits and profits. Research Limitations: This study employs a non-probability sampling method, which restricts the generalizability of our findings to only a few manufacturing public sector undertakings (PSUs) in India. The researcher focused on a case study of one PSU and did not include all manufacturing PSUs across the country. Future research could explore various key sectors within Indian public services, such as construction, IT/software, agriculture, education, government, healthcare, mining and exploration, oil and gas, finance, and other services.